Tecnología financiera para optimizar la gestión de la innovación de las pequeñas y medianas empresas en Chimbote - Espinoza Rodríguez, Olenka Ana Catherine (2022)
Conferencia de la 2nd LACCEI International Multiconference on Entrepreneurship, Innovation and Regional Development - LEIRD 2022: “Exponential Technologies and Global Challenges: Moving toward a new culture of entrepreneurship and innovation for sustainable”, Virtual Edition, December 5 – 7.